Tropical snakebite - Harrison, Robert (Henry Stewart Talks, 2020)
The global disease burden of tropical snakebite, Snakebite as a cause and consequence of tropical poverty, The medical neglect of snakebite by key health policy decision makers, The EchiTAb Study Group, Research and interventions in rural, remote tropical regions, The need for advocacy to implement sustained benefits for tropical snakebite victims